The Effect of Convolvulus arvensis Dried Extract as a Potential Antioxidant in Food Models - Nurul Aini, Mohd Azman; Gallego, Maria Gabriela; Julia, Luis; Fajari, Lluis; Almajano, María Pilar (MDPI AG, 2015)
In this study, the antioxidant activity of the Convolvulus arvensis Linn (CA) ethanol extract has been evaluated by different ways. The antioxidant activity of the extract assessed by 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation, the oxygen radical absorbance capacity (ORAC) and the ferric reducing antioxidant power (FRAP) was 1.62 mmol Trolox equivalents (TE)/g DW, 1.71 mmol TE/g DW and 2.11 mmol TE/g DW, respectively. CA ethanol extract exhibited scavenging activity against the methoxy radical initiated by the Fenton reaction and measured by Electron Paramagnetic Resonance (EPR). The antioxidant effects of lyophilised CA measured in beef patties containing 0.1% and 0.3% (w/w) CA stored in modified atmosphere packaging (MAP) (80% O2 and 20% CO2) was determined. A preliminary study of gelatine based film containing CA showed a strong antioxidant effect in preventing the degradation of lipid in muscle food. Thus, the present results indicate that CA extract can be used as a natural food antioxidant.